16m-9n+2m+11n=

Simple and best practice solution for 16m-9n+2m+11n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 16m-9n+2m+11n= equation:


Simplifying
16m + -9n + 2m + 11n = 0

Reorder the terms:
16m + 2m + -9n + 11n = 0

Combine like terms: 16m + 2m = 18m
18m + -9n + 11n = 0

Combine like terms: -9n + 11n = 2n
18m + 2n = 0

Solving
18m + 2n = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-2n' to each side of the equation.
18m + 2n + -2n = 0 + -2n

Combine like terms: 2n + -2n = 0
18m + 0 = 0 + -2n
18m = 0 + -2n
Remove the zero:
18m = -2n

Divide each side by '18'.
m = -0.1111111111n

Simplifying
m = -0.1111111111n

See similar equations:

| x(5x+19)=4 | | 4(d+5.2)=10d-6.2 | | 7x+6y=-2 | | 0=16t^2+3 | | k^2+9k+8=0 | | 6.5(y-5)=6.2-y | | 0=-16t^2+20t+3 | | 3(x+5)=9x-24 | | 5-n=7 | | 8(x+3)=5x+45 | | 12[z-7]=60 | | 3k^2+25k+8=0 | | 2.4x+67=3.9x+25 | | 16m-9n+2m+11m= | | (x+8)(9x+11)=0 | | 16x^2-4x-20=0 | | x^2-1x+5=0 | | 4(x-1)-4=0 | | 2.4x+6.7=3.9x+25 | | -43+2y+3=2(3y-4)-4 | | 12x^2+11x+2=0 | | -6(5x+4)= | | 9x+17-8x=-6-12 | | 5y-5=16+10y | | 16x^2-16x-5=0 | | -4x+1+5x=-4+9 | | 8x^2=4-9x | | 8(c+5)= | | -25.5+0.1p=0.9p+5.3 | | -2-12=5x+16-4x | | 3=-gt^2+20t+16 | | 5x^2-5x-10=0 |

Equations solver categories